HUBUNGAN ANTARA PERSEPSI GAYA KEPEMIMPINAN DAN KEPUASAN KERJA DENGAN TURNOVER INTENTION PADA KARYAWAN DEPARTEMEN MARKETING - Andy Juniar Rachman; Agus Wahyudi; Dodik Susanto; Laili Ainur Rofa; Satrya Milleneo Risky (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This research aims to examine the relationship between perceived leadership style, job satisfaction, and turnover intention among employees in the marketing department. The method used is a literature review, where data is collected through identifying and collecting relevant scientific articles. The research results show that the transformational leadership style has a positive influence on job satisfaction and a negative influence on turnover intention. In addition, job satisfaction functions as a mediator in the relationship between perceived leadership style and turnover intention, where employees who are satisfied with their jobs tend to have lower intentions to leave the company. This research recommends the importance of implementing a supportive leadership style and managing job satisfaction in order to reduce the level of turnover intention among marketing employees.